A full-scale timbrel cross vault subjected to vertical cyclical displacements in one of its supports. (15th March 2019) - Torres, Benjamín; Bertolesi, Elisa; Calderón, Pedro A.; Moragues, Juan J.; Adam, Jose M.
Graphical abstract: Highlights: Experimental test of a full scale masonry timbrel cross vault with cyclic settlements. Provides significant information about the displacement capacity of cross vaults. Discussion of the experimental results and the failure mechanism. Evaluation of the crack patterns when upward/downward settlements are applied. Abstract: Up-and-down cyclical displacement of supports-foundations, due for example to the presence of expansive soils, can affect the integrity of a structure and may even lead to its collapse. A recent study carried out at the ICITECH laboratories of the Universitat Politècnica de València analysed the effects of soil settlements on the behaviour of masonry cross vaults. One of the tests involved the construction and testing of a full-scale timbrel cross vault, one of whose supports was subjected to up-and-down vertical displacement cycles. The 4 × 4 m 2 vault was composed of four 3.6 m diameter arches supporting a masonry web. Vertical displacements were applied to one of the supports by means of two synchronised mechanical jacks. The results of the tests provide valuable information to the scientific community, architects and engineers on the behaviour of timbrel cross vaults when one of their supports is subjected to cyclical movements.